2014
DOI: 10.1108/emjb-04-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ intention to maintain quality certification

Abstract: Purpose – The purpose of this paper is to explore farmers’ intention to stay under a quality certification scheme, and the factors that impact this intention. Design/methodology/approach – Combining the agricultural household approach with the value concept, the paper analyses farmers’ intention using field research data. The improvements farmers observe after certification are viewed as utilities the farm household derives, which have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…This encourages a firm to improve in terms of quality. In short, this suggests that the pursuit for HFSC is motivated by the need to improve internal processes, increase efficiency and the determination to improve production and product quality (Fotopoulos et al , 2010; Macheka et al , 2013; Karipidis and Tselempis, 2014; Maldonado-Siman et al , 2014; Zailani et al , 2015). Furthermore, firms are eager to become certified because they want to standardise their internal operations by standardising work procedures (Fotopoulos et al , 2010), standardising documentation (Lo and Chang, 2007), formalising internal system (Terziovski et al , 2003) and by increasing consistency in operations (Buttle, 1997).…”
Section: Motivation To Halal Food Safety Certificatementioning
confidence: 99%
See 2 more Smart Citations
“…This encourages a firm to improve in terms of quality. In short, this suggests that the pursuit for HFSC is motivated by the need to improve internal processes, increase efficiency and the determination to improve production and product quality (Fotopoulos et al , 2010; Macheka et al , 2013; Karipidis and Tselempis, 2014; Maldonado-Siman et al , 2014; Zailani et al , 2015). Furthermore, firms are eager to become certified because they want to standardise their internal operations by standardising work procedures (Fotopoulos et al , 2010), standardising documentation (Lo and Chang, 2007), formalising internal system (Terziovski et al , 2003) and by increasing consistency in operations (Buttle, 1997).…”
Section: Motivation To Halal Food Safety Certificatementioning
confidence: 99%
“…Additionally, top management awareness and concern for quality is an important drive for halal certification. Furthermore, the leadership traits possessed by managers strengthen the quest for HFSC and influence a firm’s decision to maintain certification (Karipidis and Tselempis, 2014). The commitment of top management is perhaps the most important internal element for the successful implementation of FSC (Wilcock et al , 2011) Taken together, findings from past FSC literature could potentially indicate that commitment from the top management is key to the success of HFSC implementation.…”
Section: Motivation To Halal Food Safety Certificatementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating the factors of the internal business environment that have an impact on farmers' certification-related decisions also identified some market and public policy factors (Karipidis et al 2009;Asfaw et al 2010a, b;Masakure et al 2011;Muriithi et al 2011;Kersting and Wollni 2012;Karipidis and Tselempis 2014;Soltani et al 2014;Veldstra et al 2014). We select thirteen factors of the external business environment identified in these studies and we also add three factors that we identified in some in-depth interviews with producers as crucial in order to examine the research hypotheses.…”
Section: Qms Implementation and Qas Choice Modelsmentioning
confidence: 99%
“…Since the quality of the finished food depends substantially on the quality of the primary agricultural products, some studies have dealt with the adoption and implementation of QMS decisions in agriculture and each of them identified a number of determinants of such decisions (Karipidis et al 2009;Asfaw et al 2010a, b;Masakure et al 2011;Muriithi et al 2011;Kersting and Wollni 2012;Karipidis and Tselempis 2014;Soltani et al 2014;Veldstra et al 2014). These studies analyse the adoption/nonadoption and implementation/non-implementation decisions focusing mostly on factors of the internal business environment, adding also, in some cases, one or more factors from the market and/or policy.…”
Section: Introductionmentioning
confidence: 99%